Negative electrode with three-dimensional structure, preparation method and application
By preparing the negative electrode of zinc air battery with a three-dimensional structure, the problem of dendrites and low circulation efficiency on the electrode surface is solved, and a longer cycle operation cycle and higher stable circulation efficiency are achieved.
Patent Information
- Application Number
- CN202311192636.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
AI Technical Summary
In zinc-air batteries, dendrites form on the electrode surface, short cycle operation period and low stable cycle efficiency.
The negative electrode with a three-dimensional structure is prepared by precision casting, machining or three-dimensional printing, and the macroscopic surface has regular pores or the microscopic surface has regular texture.
The current distribution on the electrode surface is improved, dendrites are suppressed, and the stable electrode structure is maintained, which improves the circulation cycle and stable circulation efficiency of zinc air batteries.
Smart Images

Figure CN119650588A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a negative electrode with a three-dimensional structure, a preparation method and an application thereof. Background Art
[0002] Transforming energy structure and vigorously developing new energy storage have become a trend. Rechargeable zinc-air batteries have an ultra-high theoretical energy density of 1350Wh·kg -1 , excellent safety performance and low cost advantages, making it a research hotspot in large-scale energy storage and power conversion technology.
[0003] Zinc-air batteries consist of a zinc negative electrode and a catalytic air positive electrode separated by an electrolyte. The air positive electrode uses oxygen from the air to combine with hydrogen ions in the electrolyte to form water, while releasing electrons that can be used to do work, such as powering a device. One of the main advantages of zinc-air batteries is their high energy density. They can store a large amount of energy in a relatively small space, which makes them ideal for use in applications where weight and size are important, such as in portable electronics or electric vehicles.
[0004] However, zinc-air battery technology also has some challenges. The main problem is that the battery cannot be fully charged, and the zinc negative electrode will gradually degrade over time, which may limit the service life of the battery. At present, the negative electrode materials in zinc-air batteries are still mainly metallic zinc and its oxides, including zinc plates, zinc pastes and zinc foils. During the battery cycle charge and discharge process, zinc not only participates in the electrode reaction as an active substance, but also collects charge as a current collector. When the battery is discharged, the zinc on the electrode surface dissolves and enters the electrolyte in an ionic state. When charging, the ionic zinc in the solution is reduced to the electrode surface. Therefore, during repeated charge and discharge, the surface morphology and structure of the negative electrode will change significantly, affecting the charge collection and current distribution of the negative electrode. The uneven distribution of current and the concentration polarization of the electrolyte will cause the ionic zinc to be unevenly deposited on the electrode surface during charging, thereby forming dendrites, affecting the electrochemical performance and life of the battery. In addition, as the battery is charged and discharged, the shape and volume of the zinc negative electrode may change over time, which may cause mechanical stress and reduce the performance of the battery over time.
[0005] At present, the main solutions include surface and structural modification of zinc negative electrode and electrolyte modification, such as introducing inorganic materials to coat the surface of zinc electrode and adding surfactants to the electrolyte. However, these methods can only alleviate the morphological and structural changes of zinc negative electrode to a certain extent, and cannot fundamentally solve the problems of low cycle operation period and stable cycle efficiency caused by electrode deformation.
[0006] Therefore, as the number of battery cycles increases, it is necessary to develop a zinc electrode suitable for rechargeable zinc-air batteries to improve the cycle operation period and stabilize the cycle efficiency of rechargeable zinc-air batteries to meet the growing demand for the use of rechargeable zinc-air batteries. Summary of the invention
[0007] In view of the shortcomings of the prior art described above, the purpose of the present invention is to provide a negative electrode with a three-dimensional structure, a preparation method and an application, so as to solve the problems of dendrite formation on the electrode surface, low cycle operation period of the battery and low stable cycle efficiency in the prior art.
[0008] To achieve the above objectives and other related objectives, the present invention provides a negative electrode with a three-dimensional structure, which is prepared by the preparation method as described above, wherein the macroscopic surface of the negative electrode has regular pores, or the microscopic surface of the negative electrode has regular textures.
[0009] The present invention also provides a method for preparing a negative electrode having a three-dimensional structure, comprising any one of the following methods:
[0010] Method 1: Precision casting, machining or 3D printing of zinc, zinc alloy or conductive material without zinc, cleaning, heating, annealing and surface treatment are performed to obtain a negative electrode with regular pores on the macroscopic surface;
[0011] Method 2: Wash and dry zinc, zinc alloy or conductive material without zinc for pretreatment, etch the pretreated material, wash and dry it again to obtain a negative electrode with a regular texture on the microscopic surface.
[0012] The present invention also provides a zinc-air battery, comprising the negative electrode with the three-dimensional structure as described above.
[0013] As described above, the negative electrode with a three-dimensional structure, the preparation method and the application thereof of the present invention have the following beneficial effects:
[0014] 1. The negative electrode of the present invention has a three-dimensional structure, and its macroscopic surface regular pores or microscopic surface regular texture structure helps to improve the current distribution on the electrode surface, induce zinc to deposit uniformly on the electrode surface, thereby inhibiting the growth of dendrites. The three-dimensional porous structure negative electrode maintains a stable electrode structure during the cyclic charge and discharge process.
[0015] 2. The negative electrode of the present invention has a three-dimensional structure with controllable shape and a large specific surface area. Its porous structure is conducive to the mass transfer process. When applied to zinc-air batteries, it can increase the loading amount of zinc on the current collector, increase the battery energy density, and show excellent deposition effect during long-term operation.
[0016] 3. The negative electrode with a three-dimensional structure of the present invention is used as the negative electrode of the zinc air electrode, which can maintain a uniform current distribution at the zinc negative electrode, thereby inhibiting the formation of dendrites on the electrode surface and improving the life attenuation of the battery caused by deformation of the negative electrode structure during the cycle charge and discharge process.
[0017] 4. The preparation method of the present invention is suitable for the construction of various types of aqueous zinc-based battery negative electrodes, and provides a universal method for the design of zinc-based three-dimensional negative electrode structures. The negative electrode with a three-dimensional structure of the present invention is applied to zinc-air batteries, and a large current density of 20 mA / cm 2 The stable operation results are as follows: the single charge and discharge time is greater than 2 hours, and the total number of cycles is greater than 400, which lays a good foundation for the stable operation of aqueous zinc-based batteries in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It shows the battery charge and discharge cycle performance diagram after the non-zinc current collector constructs a microscopic three-dimensional negative electrode structure in Example 1 of the present invention.
[0019] Figure 2 It shows the battery charge and discharge cycle performance diagram after zinc is used as the negative electrode to construct a microscopic three-dimensional negative electrode structure in Example 2 of the present invention.
[0020] Figure 3 Shown is a schematic diagram of the method of using 3D printing to prepare a macroscopic regular pore multilayer structure of a nickel-iron or nickel-zinc or zinc-iron current collector according to the present invention.
[0021] Figure 4 Shown is the charge and discharge cycle performance diagram of the negative electrode prepared in Examples 3 to 4 of the present invention.
[0022] Figure 5 It shows the three-dimensional negative electrode structure with macroscopic regular pores prepared in Example 5 of the present invention.
[0023] Figure 6 The macroscopic regular pore three-dimensional negative electrode structure constructed in Example 5 of the present invention is shown in the battery at 10 mA / cm 2 Charging, 20mA / cm 2 The results of the discharge cycle test. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0025] Please refer to the attached drawings. It should be noted that the illustrations provided in this embodiment are only used to illustrate the basic concept of the present invention in a schematic manner, and the drawings only show the components related to the present invention rather than the number, shape and size of the components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0026] A first aspect of the present invention provides a negative electrode with a three-dimensional structure, wherein the macroscopic surface of the negative electrode has regular pores, or the microscopic surface of the negative electrode has regular textures.
[0027] In the present invention, the macroscopic refers to the millimeter level, and the microscopic refers to the micrometer and nanometer levels.
[0028] The negative electrode material is selected from one or more of zinc, zinc alloy or conductive materials not containing zinc. The conductive materials not containing zinc are selected from one or more of iron, stainless steel and nickel.
[0029] The pores are square or circular.
[0030] The pores have a diameter of 0.3-1.5 mm, 0.3-0.5 mm, 0.5-0.7 mm, 0.9-1.1 mm, 1.1-1.3 mm or 1.3-1.5 mm. The regular pores refer to pores arranged regularly, such as a rectangular array arrangement, a circular array arrangement, and the like.
[0031] The texture is in the form of stripes.
[0032] The width of the texture is 1-100 μm, 1-10 μm, 10-20 μm, 20-30 μm, 30-40 μm, 40-50 μm, 50-60 μm, 60-70 μm, 70-80 μm, 80-90 μm, 90-100 μm.
[0033] The spacing of the texture is 1-100 μm, 1-10 μm, 10-20 μm, 20-30 μm, 30-40 μm, 40-50 μm, 50-60 μm, 60-70 μm, 70-80 μm, 80-90 μm, 90-100 μm.
[0034] The width and spacing of the texture can be controlled by etching time.
[0035] A second aspect of the present invention provides a method for preparing a negative electrode having a three-dimensional structure as described above, comprising any one of the following methods:
[0036] Method 1: Precision casting, machining or 3D printing of zinc, zinc alloy or conductive material without zinc, cleaning, heating, annealing and surface treatment are performed to obtain a negative electrode with regular pores on the macroscopic surface;
[0037] Method 2: Wash and dry zinc, zinc alloy or conductive material without zinc for pretreatment, etch the pretreated material, wash and dry it again to obtain a negative electrode with a regular texture on the microscopic surface.
[0038] In the method for preparing a negative electrode with a three-dimensional structure of the present invention, in method 1, the cleaning is ultrasonic cleaning.
[0039] The cleaning solution is selected from deionized water or other electrode cleaning agents. The three-dimensional negative electrode initially obtained by precision casting, machining or three-dimensional printing is cleaned to remove any residues that may remain on its surface, such as oxides, unreacted metal powder or other possible contaminants. The other electrode cleaning agent is dilute nitric acid or dilute hydrochloric acid.
[0040] The heating is heating to 80-900°C, 80-100°C, 100-150°C, 150-200°C, 200-250°C, 250-300°C, 300-350°C, 350-400°C, 400-450°C, 450-500°C, 500-550°C, 550-600°C, 600-650°C, 650-700°C, 700-750°C, 750-800°C, 800-850°C or 850-900°C.
[0041] The heating rate is 20-100°C / h, 20-30°C / h, 30-40°C / h, 40-50°C / h, 50-60°C / h, 60-70°C / h, 70-80°C / h, 80-90°C / h or 90-100°C / h.
[0042] The annealing rate is 20-50°C / h, 20-25°C / h, 25-30°C / h, 30-35°C / h, 35-40°C / h, 40-45°C / h or 45-50°C / h. Annealing is a cooling process of controlling the cooling rate, which can help release residual stress, optimize grain structure, and improve electrode performance.
[0043] The surface treatment method is chemical etching or physical deposition. The three-dimensional negative electrode surface obtained initially is treated to remove defects on the electrode surface or remove the oxide layer on the electrode surface to further improve its electrochemical performance.
[0044] The specific process of method one is: preliminarily constructing a three-dimensional negative electrode through precision casting, mechanical processing or three-dimensional printing technology, cleaning the preliminarily obtained three-dimensional negative electrode with deionized water or other electrode cleaning agents, and then heating it at a rate of 20 to 100°C / h to 80 to 900°C, and annealing it at a rate of 20 to 100°C / h. Finally, chemical etching or physical deposition is used to process the electrode surface again to obtain a negative electrode with regular pores on the macroscopic surface.
[0045] In the preparation method of the negative electrode with a three-dimensional structure of the present invention, in method 2, the washing is ultrasonic cleaning using deionized water and organic solvent I in sequence. Wherein, the organic solvent is selected from one or more of ethanol and isopropanol. In a preferred embodiment of the present invention, the washing is ultrasonic cleaning in deionized water, ethanol, and isopropanol in sequence. The ultrasonic time is 10 to 60 min, 10 to 15 min, 15 to 20 min, 20 to 25 min, 25 to 30 min, 30 to 35 min, 35 to 40 min, 40 to 45 min, 45 to 50 min, 50 to 55 min or 55 to 60 min.
[0046] The drying is vacuum drying. The drying temperature is 20-70°C, 20-25°C, 25-30°C, 30-35°C, 35-40°C, 40-45°C, 45-50°C, 50-55°C, 55-60°C, 60-65°C or 65-70°C.
[0047] In the preparation method of the negative electrode with a three-dimensional structure of the present invention, in method 2, the pretreatment is to polish the surface of zinc, zinc alloy or zinc-free conductive material with sandpaper; or soak the zinc, zinc alloy or zinc-free conductive material in an acid solution.
[0048] Wherein, the mesh number of the sandpaper is 50-400 mesh, 50-100 mesh, 100-150 mesh, 150-200 mesh, 200-250 mesh, 250-300 mesh, 300-350 mesh or 350-400 mesh.
[0049] The grinding time is 2 to 20 min, 2 to 4 min, 4 to 6 min, 6 to 8 min, 8 to 10 min, 10 to 12 min, 12 to 14 min, 14 to 16 min, 16 to 18 min or 18 to 20 min.
[0050] The acid solution is selected from one or more of hydrochloric acid, sulfuric acid and nitric acid.
[0051] The concentration of the acid solution is 0.2-2 mol / L, 0.2-0.4 mol / L, 0.4-0.6 mol / L, 0.6-0.8 mol / L, 0.8-1.0 mol / L, 1.0-1.2 mol / L, 1.2-1.4 mol / L, 1.4-1.6 mol / L, 1.6-1.8 mol / L or 1.8-2.0 mol / L.
[0052] The soaking time is 5 to 120 min, 5 to 10 min, 10 to 20 min, 20 to 30 min, 30 to 40 min, 40 to 50 min, 50 to 60 min, 60 to 70 min, 70 to 80 min, 80 to 90 min, 90 to 100 min, 100 to 110 min or 110 to 120 min.
[0053] In the method for preparing a negative electrode with a three-dimensional structure of the present invention, in method 2, the etching is carried out in an organic acid solution, and the organic acid solution is formed by dispersing an organic acid in an organic solvent II. The etching time is 2 to 48 hours, 2 to 5 hours, 5 to 10 hours, 10 to 15 hours, 15 to 20 hours, 20 to 25 hours, 25 to 30 hours, 30 to 35 hours, 35 to 40 hours, 40 to 45 hours or 45 to 48 hours. Wherein, the concentration of the organic acid solution is 0.2 to 2 mol / L, 0.2 to 0.4 mol / L, 0.4 to 0.6 mol / L, 0.6 to 0.8 mol / L, 0.8 to 1.0 mol / L, 1.0 to 1.2 mol / L, 1.2 to 1.4 mol / L, 1.4 to 1.6 mol / L, 1.6 to 1.8 mol / L or 1.8 to 2.0 mol / L.
[0054] The organic acid is selected from one or more of citric acid, trifluoromethanesulfonic acid and trinitrobenzenesulfonic acid.
[0055] The organic solvent II is selected from one or more of acetonitrile, N-methylpyrrolidone, and N,N-dimethylformamide.
[0056] The second cleaning after etching is ultrasonic cleaning in an organic solvent III. The organic solvent III is selected from one or more of acetonitrile and ethanol.
[0057] The specific process of method 2 is: ultrasonically clean zinc, zinc alloy or zinc-free conductive material in deionized water and organic solvent in turn, perform surface pretreatment to remove the surface oxide layer after drying, obtain the pretreated electrode sheet after cleaning and drying, place the pretreated electrode sheet in an organic acid solution for etching, then take out, clean and dry to obtain a negative electrode with a regular texture on the microscopic surface.
[0058] Among them, the two cleaning and drying methods are the same. Cleaning is ultrasonic cleaning in deionized water and anhydrous ethanol in sequence. The cleaning time is 10-60min, 10-15min, 15-20min, 20-25min, 25-30min, 30-35min, 35-40min, 40-45min, 45-50min, 50-55min or 55-60min. The drying condition is vacuum drying. The drying temperature is 20-70℃, 20-25℃, 25-30℃, 30-35℃, 35-40℃, 40-45℃, 45-50℃, 50-55℃, 55-60℃, 60-65℃ or 65-70℃.
[0059] A third aspect of the present invention provides a zinc-air battery, comprising the negative electrode with a three-dimensional structure as described above.
[0060] Example 1
[0061] Preparation of a negative electrode with a regular texture on the microscopic surface:
[0062] 1. Select a 55*55 stainless steel sheet as the base material, place it in deionized water, ethanol, and isopropanol solutions in turn, ultrasonicate for 15 minutes respectively, and then vacuum dry it at 40°C for 6 hours.
[0063] 2. Use 200-grit sandpaper to polish the surface of the stainless steel sheet to remove the surface oxide layer. After polishing, place the stainless steel sheet in water and ethanol for ultrasonic cleaning for 15 minutes respectively, and then vacuum dry it at 40°C for 6 hours.
[0064] 3. Disperse trifluoromethanesulfonic acid evenly in acetonitrile solution as an acid etching solution with a concentration of 0.5 mol / L; soak the pretreated stainless steel sheet in 20 mL of the acid etching solution for 24 h, take it out and ultrasonically clean it in acetonitrile and ethanol solutions for 30 min, and dry it in a vacuum oven at 40°C for 6 h to obtain a negative electrode with a microscopic surface having a regular striped texture with a width of 90 to 100 μm and a spacing of 90 to 100 μm.
[0065] The surface of the organic acid-etched metal plate obtained in Example 1 has a certain microscopic regular texture. The negative electrode material prepared in this example is assembled into a zinc-air battery for cyclic charge and discharge performance testing. The battery is 10 mA / cm 2 Charging 20mA / cm 2 The discharge cycle is tested, and the charge and discharge cycle curve is shown in the attached Figure 1 As shown in the figure, after the battery has been working continuously for 120 hours, the discharge voltage is still around 1V.
[0066] Example 2
[0067] Preparation of a negative electrode with a regular texture on the microscopic surface:
[0068] 1. Select a 55*55 zinc plate as the base material, place it in deionized water, ethanol, and isopropanol solutions in turn, ultrasonicate for 15 minutes respectively, and then vacuum dry it at 60℃ for 6 hours.
[0069] 2. Use 200-grit sandpaper to polish the surface of the zinc plate to remove the surface oxide layer. After polishing, place the zinc plate in water and ethanol for ultrasonic cleaning for 15 minutes respectively, and then vacuum dry it at 60°C for 6 hours.
[0070] 3. Disperse trifluoromethanesulfonic acid evenly in acetonitrile solution as an acid etching solution with a concentration of 0.5 mol / L; soak the pretreated zinc plate in 20 mL of the acid etching solution for 48 h, take it out and ultrasonically clean it in acetonitrile and ethanol solutions for 30 min, and dry it in a vacuum oven at 60°C for 6 h to obtain a negative electrode with a microscopic surface having a regular striped texture with a width of 90 to 100 μm and a spacing of 90 to 100 μm.
[0071] Compared with the untreated zinc plate negative electrode, the negative electrode with a three-dimensional structure with regular microscopic surface texture obtained in Example 2 has a significant dendrite inhibition effect and a reduced consumption rate of the zinc plate. The negative electrode material prepared in this example is assembled into a zinc-air battery for cycle charge and discharge performance testing. The battery is charged at 10 mA / cm 2 Charging, 20mA / cm 2 The discharge cycle is tested and the single discharge time can be greater than 2 hours. Figure 2 shown.
[0072] Example 3
[0073] Preparation of a negative electrode with regular pores on the macroscopic surface:
[0074] 1. Use a 3D printer to print a nickel-iron three-layer current collector with regular holes, the hole diameter is 0.5mm, and the thickness of each layer is 1mm;
[0075] 2. Use dilute nitric acid to clean the surface of the current collector;
[0076] 3. Place the cleaned current collector in a 1 mol / L zinc sulfate electrolyte and use 20 mA / cm 2 The surface electrochemical deposition was carried out at a current density of 500 nm for 5 h, and a negative electrode with regular pores of 0.5 mm on the macroscopic surface was obtained.
[0077] The negative electrode with regular pores on the macroscopic surface prepared in Example 3 was used as the negative electrode of the zinc-air battery. The battery was charged at 10 mA / cm 2 Charging, 10mA / cm 2 The discharge cycle was tested and the results are shown in the attached Figure 4 shown.
[0078] Example 4
[0079] Preparation of negative electrode with regular pores on the macroscopic surface:
[0080] The same method as in Example 3 was used to prepare current collectors with pore sizes of 0.8 mm, 1.0 mm, 1.2 mm, and 1.5 mm, respectively, and the post-processing steps were the same as in Example 3 to obtain negative electrodes with pore sizes of 0.8 mm, 1.0 mm, 1.2 mm, and 1.5 mm on the macroscopic surface.
[0081] The negative electrodes with different pore sizes prepared in Example 4 were used as negative electrodes of zinc-air batteries. The batteries were charged at 10 mA / cm 2 Charging, 10mA / cm 2 The discharge cycle is tested. Figure 4 As shown, the life of the prepared negative electrode with a pore size of 1.2 mm was significantly improved, exceeding 1000 hours.
[0082] Example 5
[0083] Preparation of a negative electrode with regular pores on the macroscopic surface:
[0084] 1. Using mechanical processing methods, regular hole current collectors were etched on the surfaces of different nickel-iron plates, with pore sizes of 0.3 mm, 0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm, and 1.5 mm respectively;
[0085] 2. Use dilute nitric acid to clean the surface of the current collector;
[0086] 3. Place the cleaned current collector in a 1 mol / L zinc sulfate electrolyte and use 20 mA / cm 2 The surface electrochemical deposition was carried out at a current density of 500 nm for 5 h to obtain a negative electrode with regular pores on the macroscopic surface with pore sizes of 0.3 mm, 0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm and 1.5 mm respectively.
[0087] Using zinc-air battery at 10mA / cm 2 Charging, 20mA / cm 2 Discharge cycle test, as shown in the attached Figure 6 As shown, the test cycle time of the negative electrode with a pore size of 1.2 mm reaches 400 hours; and within the pore size range of 0.3 to 1.5 mm, the same test method is used, and the cycle time of the negative electrode with other pore sizes can reach 400 hours.
[0088] Example 6
[0089] Preparation of a negative electrode with regular pores on the macroscopic surface:
[0090] 1. Use a special metal etching solution to etch a regular hole current collector on the surface of the nickel-iron plate, where the pore size is between 0.3 and 1.5 mm;
[0091] 2. Use dilute nitric acid to clean the surface of the current collector;
[0092] 3. Place the cleaned current collector in a 1 mol / L zinc sulfate electrolyte and use 20 mA / cm 2 The surface electrochemical deposition was carried out at a current density of 500 nm for 5 h to obtain a negative electrode with regular pores on the macroscopic surface.
[0093] The negative electrode prepared in Example 6 was used in a zinc-air battery at 10 mA / cm 2 Charging, 20mA / cm 2 The discharge cycle is tested and the cycle time can reach more than 400 hours.
[0094] Example 7
[0095] Preparation of a negative electrode with regular pores on the macroscopic surface:
[0096] 1. Use laser etching to etch regular holes on the surface of the nickel-iron plate, where the pore size is between 0.3 and 1.5 mm;
[0097] 2. Use dilute nitric acid to clean the surface of the current collector;
[0098] 3. Place the cleaned current collector in a 1 mol / L zinc sulfate electrolyte and use 20 mA / cm 2 The surface electrochemical deposition was carried out at a current density of 500 nm for 5 h to obtain a negative electrode with regular pores on the macroscopic surface.
[0099] The negative electrode prepared in Example 7 was used in a zinc-air battery at 10 mA / cm 2 Charging, 20mA / cm 2 The discharge cycle is tested and the cycle time can reach more than 400 hours.
[0100] Comparative Example 1
[0101] Preparation of a 2D Fe-Ni-Zn anode:
[0102] 1. Select a 55*55 stainless steel sheet as the base material, place it in deionized water, ethanol, and isopropanol solutions in turn, ultrasonicate for 15 minutes respectively, and then vacuum dry it at 40°C for 6 hours.
[0103] 2. Use 200-grit sandpaper to polish the surface of the stainless steel sheet to remove the surface oxide layer. After polishing, place the stainless steel sheet in water and ethanol for ultrasonic cleaning for 15 minutes respectively, and then vacuum dry it at 40°C for 6 hours.
[0104] 3. Place the cleaned current collector in a 1 mol / L zinc sulfate electrolyte and use 20 mA / cm 2 The surface electrochemical deposition was carried out at a current density of 5000 nm for 5 h to obtain the Fe-Ni-Zn negative electrode.
[0105] The Fe-Ni-Zn negative electrode prepared in Comparative Example 1 was used as the negative electrode of the zinc-air battery. 2 Charging, 10mA / cm 2 The discharge cycle was tested and the results are shown in the attached Figure 4 The 2D Fe-Ni-Zn negative electrode results shown have a battery charge and discharge time of <40 hours.
[0106] Comparative Example 2
[0107] Preparation of a 2D Fe / Ni-Zn anode:
[0108] 1. Select a 55*55 stainless steel sheet as the base material, place it in deionized water, ethanol, and isopropanol solutions in turn, ultrasonicate for 15 minutes respectively, and then vacuum dry it at 40°C for 6 hours.
[0109] 2. Use 200-grit sandpaper to polish the surface of the stainless steel sheet to remove the surface oxide layer. After polishing, place the stainless steel sheet in water and ethanol for ultrasonic cleaning for 15 minutes respectively, and then vacuum dry it at 40°C for 6 hours.
[0110] 3. Use dilute nitric acid or dilute hydrochloric acid to clean the surface of the current collector;
[0111] 4. Place the cleaned current collector in a 1 mol / L zinc sulfate electrolyte and use 20 mA / cm 2 The surface electrochemical deposition was carried out at a current density of 5000 nm for 5 h to obtain the Fe / Ni-Zn negative electrode.
[0112] The Fe / Ni-Zn negative electrode prepared in Comparative Example 2 was used as the negative electrode of the zinc-air battery. The battery was charged at 10 mA / cm 2 Charging, 10mA / cm 2 The discharge cycle was tested and the results are shown in the attached Figure 4 The 2D Fe / Ni-Zn negative electrode results shown have a battery charge and discharge time of <200 hours.
[0113] In summary, the pores, texture size or width of the three-dimensional structured negative electrode prepared by the preparation method of the present invention can be adjusted, and the current distribution can be adjusted by controlling the size of the pores and textures in the three-dimensional negative electrode structure, thereby improving the service life of the zinc anode; the three-dimensional structured negative electrode of the present invention is suitable for the construction of various types of aqueous zinc-based battery negative electrodes, and provides a universal method for the design of zinc-based three-dimensional negative electrode structures. Therefore, the present invention effectively overcomes various shortcomings in the prior art and has a high industrial utilization value.
[0114] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A negative electrode having a three-dimensional structure, characterized in that: The negative electrode macroscopic surface has regular pores, or the negative electrode microscopic surface has regular textures.
2. The negative electrode having a three-dimensional structure according to claim 1, characterized in that: The material of the negative electrode is selected from one or more of zinc, zinc alloy or conductive material not containing zinc; And / or, the pores are square or circular; And / or, the pores have a pore size of 0.3 to 1.5 mm; and / or, the texture is striped; and / or, the width of the texture is 1 to 100 μm; And / or, the spacing of the textures is 1 to 100 μm.
3. A method for preparing a negative electrode having a three-dimensional structure as claimed in any one of claims 1 to 2, characterized in that: This includes any of the following methods: Method 1: Precision casting, machining or 3D printing of zinc, zinc alloy or conductive material without zinc, cleaning, heating, annealing and surface treatment are performed to obtain a negative electrode with regular pores on the macroscopic surface; Method 2: Wash and dry zinc, zinc alloy or conductive material without zinc for pretreatment, etch the pretreated material, wash and dry it again to obtain a negative electrode with a regular texture on the microscopic surface.
4. The preparation method according to claim 3, characterized in that: In method 1, the cleaning is ultrasonic cleaning; And / or, in method 1, the cleaning solution is selected from deionized water or other electrode cleaning reagents; And / or, in method 1, the heating is heating to 80-900° C.; And / or, in method 1, the heating rate is 20 to 100° C. / h; And / or, in method 1, the annealing rate is 20 to 50°C / h; And / or, in method 1, the surface treatment method is chemical etching or physical deposition.
5. The preparation method according to claim 3, characterized in that: In method 2, the washing is performed by ultrasonic cleaning using deionized water and organic solvent I in sequence; And / or, in method 2, the drying is vacuum drying; And / or, in method 2, the drying temperature is 20-70°C.
6. The preparation method according to claim 3, characterized in that: In the second method, the pretreatment is to polish the surface of zinc, zinc alloy or conductive material without zinc by using sandpaper; or to soak zinc, zinc alloy or conductive material without zinc in an acid solution.
7. The preparation method according to claim 6, characterized in that: The mesh number of the sandpaper is 50 to 400 meshes; And / or, the grinding time is 2 to 20 minutes; And / or, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid, and nitric acid; and / or, the concentration of the acid solution is 0.2 to 2 mol / L; And / or, the soaking time is 5 to 120 minutes.
8. The preparation method according to claim 3, characterized in that: In method 2, the etching is performed in an organic acid solution, and the organic acid solution is formed by dispersing an organic acid in an organic solvent II; And / or, in method 2, the etching time is 2 to 48 hours; And / or, in method 2, the re-cleaning after etching is ultrasonic cleaning in organic solvent III.
9. The preparation method according to claim 8, characterized in that: The concentration of the organic acid solution is 0.2-2 mol / L; And / or, the organic acid is selected from one or more of citric acid, trifluoromethanesulfonic acid, and trinitrobenzenesulfonic acid; And / or, the organic solvent II is selected from one or more of acetonitrile, N-methylpyrrolidone, and N,N-dimethylformamide; And / or, the organic solvent III is selected from one or more of acetonitrile and ethanol.
10. A zinc-air battery, characterized in that: The invention comprises a negative electrode having a three-dimensional structure as claimed in any one of claims 1 to 2.